Functional Outcomes of a Patient With Acute Paraplegia After Open Heart Surgery: A Case Report. Issue 4 (October 2016) - Irons, Sonya L.; Hoffman, Julie E.
Abstract : Introduction: Paraplegia is a complication that may occur after open heart surgery. Minimal published research exists regarding functional outcomes for this patient population. The purpose of this case report is to describe the physical therapy management, including functional outcomes, as defined by the FIM instrument, before and after rehabilitation for a patient who developed paraplegia after open heart surgery. Case Presentation: A 69-year-old man with a past lumbar fusion presented with acute paraplegia immediately after a coronary artery bypass graft and aortic valve replacement surgery. Two months postoperatively, a neurologist determined the probable etiology to be a lumbar disc herniation. The medical charts were reviewed retrospectively. He spent 92 days in the hospital undergoing physical and occupational therapy in acute care and inpatient rehabilitation. He did not regain function in his lower extremities, and a power wheelchair became his primary mode of mobility. The patient was discharged home with his spouse as the primary caregiver. Conclusion: The patient demonstrated functional gains as evidenced by an increase of FIM total score, FIM efficacy, and FIM efficiency after multidisciplinary inpatient rehabilitation. This case report could assist health care professionals in the comprehensive rehabilitation management of this patient population regardless of etiology.